Microprograma documental que promoverá la solidaridad hacia los animales en el Perú - Lurquin Pomar, Alejandro Andre (2023)
This project consists of the realization of a documentary microprogram that seeks to promote solidarity towards animals in Peru. The content they will offer will be stories related to the difficulties they face; For this reason, a compilation of real cases evidenced in shelters and refuges has been carried out. Likewise, stories of shelters, stray animals, wild animals victims of illegal trafficking, among others, are written. Finally, the microprogram will have an “Instagram” and “Facebook” fan page for dissemination.